2006
DOI: 10.1093/ps/85.4.753
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Glucagon in Regulating Chicken Hepatic Malic Enzyme and Histidase Messenger Ribonucleic Acid Expression In Response to an Increase in Dietary Protein Intake

Abstract: Increased dietary protein intake rapidly (3 h) decreases hepatic malic enzyme and increases hepatic histidase mRNA expression in broiler chicks. A series of experiments was conducted to determine the role that glucagon or a specific mixture of dietary amino acids might have in regulating the rapid changes in mRNA expression of these enzymes, when dietary protein intake is increased. Three hours after the injection of glucagon (240 microg/kg of BW) into the brachial vein of broiler chicks, hepatic malic enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…High dietary concentrations of protein appear to increase glucagon secretion in mammals (Balage et al, 1986;Charlton et al, 1996;Gannon and Nuttall, 2004). Chendrimada et al (2006) observed increased plasma glucagon concentrations within 1 and 3 h but not at 2 h after feeding broiler chicks a diet containing 40% protein as compared with 13% protein. In previous studies in this laboratory, overnight-fasted Leghorn chicks were given access to a 19% CP diet containing nutritionally adequate or surfeit levels of all indispensable AA or the same diets supplemented with a 13.3% mixture of indispensable AA, NaHCO 3 , and glucose (Keene and Austic, 2001;Keene, 2002).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…High dietary concentrations of protein appear to increase glucagon secretion in mammals (Balage et al, 1986;Charlton et al, 1996;Gannon and Nuttall, 2004). Chendrimada et al (2006) observed increased plasma glucagon concentrations within 1 and 3 h but not at 2 h after feeding broiler chicks a diet containing 40% protein as compared with 13% protein. In previous studies in this laboratory, overnight-fasted Leghorn chicks were given access to a 19% CP diet containing nutritionally adequate or surfeit levels of all indispensable AA or the same diets supplemented with a 13.3% mixture of indispensable AA, NaHCO 3 , and glucose (Keene and Austic, 2001;Keene, 2002).…”
Section: Discussionmentioning
confidence: 78%
“…No differences in plasma glucagon concentrations between the 2 groups of chicks were detected during a 3-to 4-h period after the chicks had been given access to the diets in 3 experiments. The variable response to a 27% increment in dietary protein among the 3 sampling periods in the study of Chendrimada et al (2006) and the results of the experiments of Keene (2002) involving the AA supplement suggest that it may be difficult to detect effects of dietary protein on glucagon secretion in chickens. It is not clear whether glucagon is involved in the regulation of chicken PAT.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that the glucagon level was significantly decreased in all NFD treatments compared to the control, as insulin and glucagon are normally perceived to operate in an opposite manner in mammals. This could be related to the nutritional composition of NFD, since there are positive relationships between dietary protein levels and plasma glucagon in chickens ( Chendrimada et al., 2006 ), and exposure to the exogenous glucose has been found to suppresses glucagon secretion ( Ma et al., 2005 ).…”
Section: Discussionmentioning
confidence: 99%